Impact of IT Leadership on Transformation of the Role of IT in Improving Individual Tax Return Reporting Compliance at the Directorate General of Taxes - Ariani, Septi; Rahmawati Wahab, Aliya; Dwi Fajar Maulana, Yudhi; Wijayanti, Fitri; Swari Mahardika, Mainar; Rifki Shihab , Muhammad (Faculty of Computer Science (FILKOM) Brawijaya University, 2024)
The Directorate General of Taxes (DGT) applies for technological advances in filing applications for Tax Return reporting (TRR), which was previously carried out manually. This enables DGT to reduce administrative work. IT is inseparable from the presence of IT leadership that can direct existing resources to get maximum results. The problems faced at DGT, there are still problems regarding late and even not submitting taxpayers TRR. It can affect the level of TRR compliance. This study aims to determine the role of IT leadership in supporting the role of IT to improve TRR compliance. The results showed that the increase in online TRR compliance was due to a massive campaign carried out by the Head Office, Regional Offices, and Tax Offices. This study indicates differences in the IT role in several phases of the TRR service development at DGT. The success of IT support in achieving TRR was inseparable from the IT Leadership approach applied at DGT. It showed that the increase in the role of IT in an organization had to be following the strengthening of IT Leadership within an organization and support to driver started from the reformation and efficiency of IT within the organization.